The True Meaning of Sacrifice - Amy Zulaikha, Mohd Ali (UMPSA, 2024)
Muslims worldwide celebrate two major annual festivals; Aidilfitri and Aidiladha, both referred to as Hari Raya in Malaysia. Hari Raya Aidilfitri is a lively celebration characterised by visits to family and friends, colourful traditional attire, and festive meals.